The Weaker Sex in War Gender and Nationalism in Civil War Virginia - Brill, Kristen (A Nation Divided, 2022)
American Civil War;Virginia;Gender History;Confederate Nationalism;Citizenship;southern women;female enslavers;Richmond Bread Riot;Mount Vernon Ladies' Association;Ladies Defense Association;Home for Needy Confederate Women